2021
DOI: 10.3390/foods10122992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kernel Size and Its Potential Interaction with Genotype on Key Quality Traits of Durum Wheat

Abstract: This study was conducted to evaluate the influence of kernel size and its potential interaction with genotype on durum wheat quality with emphases on kernel physical characteristics, milling performance, and color-related quality parameters. Wheat samples of seven genotypes, selected from the 2018 Canadian durum variety registration trial, were segregated into large (LK), medium (MK), and small-sized kernels (SK). In general, the kernel size greatly affected the durum wheat milling performance. Within a given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Drought and heat are major abiotic stresses affecting durum wheat production and quality worldwide. In addition to the yield loss, the effects of drought and heat stresses have a very significant impact on durum quality, as indicated by a lower test weight, smaller kernels, lower milling yield, and higher semolina ash [ 18 ]. Enhanced heat and drought tolerance of wheat is not only to ensure a stable yield across both good and bad seasons while maintaining a high yield under optimal conditions, but also to protect quality by minimizing their impacts on kernel morphological properties, which, in turn, adversely affect milling quality.…”
Section: Advances In the Quality Of Durum Wheatmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought and heat are major abiotic stresses affecting durum wheat production and quality worldwide. In addition to the yield loss, the effects of drought and heat stresses have a very significant impact on durum quality, as indicated by a lower test weight, smaller kernels, lower milling yield, and higher semolina ash [ 18 ]. Enhanced heat and drought tolerance of wheat is not only to ensure a stable yield across both good and bad seasons while maintaining a high yield under optimal conditions, but also to protect quality by minimizing their impacts on kernel morphological properties, which, in turn, adversely affect milling quality.…”
Section: Advances In the Quality Of Durum Wheatmentioning
confidence: 99%
“…They also suggested that kernel size uniformity is very important in the milling process with respect to cleaning, conditioning, debranning, and grinding. Recent research on the relationship of kernel size and genotype on milling performance further substantiates the importance of these aspects for the selection of appropriate durum wheat [ 18 ]. Often the semolina quality specified requires the blending of two or more wheat types to achieve the desired quality of the blend.…”
Section: Raw Materials and Semolina Millingmentioning
confidence: 99%
“…The ash content of grain is an indirect indicator of the ash content and purity of semolina. Grain with high ash content (1.18-1.24%) decreases semolina brightness and yellowness, thus compromising pasta quality [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…Grain quality is also significantly influenced by the content of the yellow pigment, a trait that is genetically conditioned, stable, and not significantly affected by agronomic or environmental factors [15,16]. The yellow pigment is associated with the presence of natural carotenoids in semolina, and it is responsible for the desirable yellow color of pasta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation